Transformative Finance: Embracing Digital Innovations for Financial Excellence - Bambang Wahyudiono; Irdha Yusra; Sri Maria Ulfha (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study investigates the impact of digital innovations on financial excellence, with a focus on the mediating roles of financial inclusion and operational efficiency. Utilizing a quantitative research design, data were collected from 150 Gopay users through an online questionnaire. The analysis, conducted using SmartPLS, reveals that digital innovations significantly enhance financial excellence both directly and indirectly through financial inclusion and operational efficiency. The findings indicate that digital innovations positively influence financial inclusion and operational efficiency, which in turn contribute to improved financial outcomes and user satisfaction. This study underscores the importance of digital innovations in driving financial excellence by enhancing access to financial services and optimizing operational processes. The results suggest that financial platforms can achieve greater financial success by strategically investing in digital technologies that promote inclusivity and operational efficiency.